Coal-based solid waste ceramsite proppant and preparation method thereof

By using coal-based solid waste ceramic proppant, combined with coal gangue, fly ash acid slag and homemade binder, the problems of high density, high cost and low strength of ceramic proppant are solved, and low density and high strength are achieved. The strength and low-cost ceram proppant preparation improves the efficiency of the fracturing process and oil and gas production.

CN119263872APending Publication Date: 2025-01-07CHINA SHENHUA ENERGY CO LTD HARWUSU OPEN-PIT COAL MINE +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411462560.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing ceramic proppants have high density, high cost and low strength, resulting in uneven distribution during fracturing and decreasing flow diversion capacity, affecting oil and gas production, and the sintering method consumes a lot of energy.

Method used

Coal-based solid waste is used as the main raw material, including coal gangue and fly ash acid slag, combined with sintering aid and a mixture of homemade silica hydrogel and polyethylene glycol or polyvinyl alcohol as the binder. Through specific proportioning and sintering processes, low-density, high-strength coal-based solid waste ceramic proppant is prepared.

Benefits of technology

It reduces the production cost of ceram proppants, achieves the combination of low density and high strength, improves the mechanical properties and flow-guiding ability of the material, reduces acid solubility, reduces production costs, and replaces the use of high-alumina raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005092248130000131
    Figure BDA0005092248130000131
Patent Text Reader

Abstract

The invention discloses a coal-based solid waste ceramsite proppant and a preparation method thereof, and relates to the technical field of coal chemical industry. The coal-based solid waste ceramsite proppant comprises a first raw material and a second raw material, the first raw material comprises the following components in percentage by mass: 60%-75% of coal gangue and 25%-40% of fly ash acid-soluble slag, totaling 100%; the second raw material comprises a sintering aid and a binder; the mass of the sintering aid is 0.5%-2.5% of the total mass of the first raw material, and the mass of the binder is 8%-10% of the total mass of the first raw material; the binder is a mixed solution of polyethylene glycol or polyvinyl alcohol and silicon dioxide hydrogel. The breakage rate of the low-density high-strength ceramsite proppant is 4%-5.3% under 35 MPa, the breakage rate of the low-density high-strength ceramsite proppant is 5%-7.4% under 52 MPa, and the low-density high-strength ceramsite proppant is low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coal chemical industry, and in particular to a coal-based solid waste ceramsite proppant and a preparation method thereof. Background Art

[0002] Fracturing is an important mining technology for developing low permeability oil and gas fields. In the fracturing process, the selection of appropriate proppants can not only provide good support for the cracks, but also effectively reduce the damage to the original cracks and form a good bonding effect with the crude oil in the cracks.

[0003] Ceramic granule proppant is a kind of fracturing proppant. It is mainly used in deep well oil field mining operations because of its advantages such as high compressive strength, good conductivity and strong corrosion resistance. Traditional granule proppant is mainly made of bauxite. The high aluminum content leads to an increase in the compressive strength of granule proppant and a corresponding increase in density. Proppants with higher density are prone to local accumulation during the pumping process, resulting in uneven distribution of proppant in the entire fracture, decreased conductivity and thus affecting oil and gas production. In addition, the increase in proppant density requires an increase in the viscosity of the fracturing fluid, which increases the performance requirements and energy consumption of the pumping equipment accordingly, resulting in an increase in production costs. In addition, the commonly used bauxite proppant uses a sintering method with a sintering temperature of 1300-1600°C, and the energy cost is also very high.

[0004] Therefore, the preparation of low-cost, low-density, high-compressive-strength expanded clay proppants is the current research focus. Summary of the invention

[0005] The main purpose of the present invention is to provide a coal-based solid waste ceramsite proppant and a preparation method thereof, so as to solve the problems of high raw material cost, high density and low strength of ceramsite proppant in the prior art.

[0006] In order to achieve the above object, according to one aspect of the present invention, a coal-based solid waste ceramsite proppant is provided, comprising a first raw material and a second raw material;

[0007] In terms of mass percentage, the first raw material includes: 60% to 75% of coal gangue, 25% to 40% of fly ash acid slag, and a total of 100%;

[0008] The second raw material includes: a sintering aid and a binder; the mass of the sintering aid is 0.5% to 2.5% of the total mass of the first raw material, and the mass of the binder is 8% to 10% of the total mass of the first raw material;

[0009] The binder is a mixture of polyethylene glycol or polyvinyl alcohol and silicon dioxide hydrogel.

[0010] Furthermore, the mass percentage of the coal gangue in the first raw material is 65% to 75%, and the mass percentage of the fly ash acid slag is 25% to 35%.

[0011] Furthermore, the mass of the sintering aid is 0.5% to 2% of the total mass of the first raw material, and the mass of the binder is 9% to 10% of the total mass of the first raw material.

[0012] Furthermore, the mass percentage of the coal gangue in the first raw material is 68% to 70%, and the mass percentage of the fly ash acid slag is 30% to 32%.

[0013] Furthermore, the mass of polyethylene glycol or polyvinyl alcohol accounts for 3% to 5% of the total mass of the mixed solution, and the remainder is silica hydrogel, which is 100% in total.

[0014] Furthermore, the raw material of the silica hydrogel is fly ash acid slag.

[0015] Furthermore, the particle size of the silica hydrogel is 10 to 20 nm.

[0016] Furthermore, the sintering aid is calcium oxide or magnesium oxide.

[0017] Furthermore, the main phase component of the coal-based solid waste ceramsite proppant is mullite phase.

[0018] Furthermore, the volume density of the coal-based solid waste ceramsite proppant is 1.25-1.46 g / cm 3 , apparent density is 1.8~2.3g / cm 3 The crushing rate at 35MPa is 4% to 6%, the crushing rate at 52MPa is 5% to 8%, the sphericity is 0.7 to 0.9, and the acid solubility is 5% to 5.3%.

[0019] Furthermore, the volume density of the coal-based solid waste ceramsite proppant is 1.25-1.4 g / cm 3 , apparent density is 1.8~2.1g / cm 3 The crushing rate at 35MPa is 4% to 5.3%, the crushing rate at 52MPa is 5% to 7.4%, the sphericity is 0.8 to 0.9, and the acid solubility is 5% to 5.28%.

[0020] According to a second aspect of the present invention, there is provided a method for preparing the above-mentioned coal-based solid waste ceramsite proppant, comprising the following steps:

[0021] Step S1: Obtaining various raw materials according to the recipe;

[0022] Step S2: mixing and granulating coal gangue, fly ash acid slag, sintering aid and binder to obtain a spherical green body;

[0023] Step S3: drying and sieving the spherical green bodies to obtain ceramsite proppant raw materials;

[0024] Step S4: The ceramsite proppant raw material is sintered to obtain a coal-based solid waste ceramsite proppant.

[0025] Furthermore, the preparation method of the binder comprises the following steps:

[0026] Step S2-1: using an alkaline solution to adjust the pH value of the fly ash acid slag solution to 8-9 to obtain a silicate solution; after the silicate solution passes through an acidic ion exchange resin, ammonia water is used to adjust the pH value to 5-6 to obtain a silica hydrogel;

[0027] Step S2-2: Add polyethylene glycol or polyvinyl alcohol to the silica hydrogel in proportion to obtain a binder.

[0028] Furthermore, the alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution.

[0029] Furthermore, the acidic ion exchange resin includes polystyrene sulfonic acid type ion exchange resin and polystyrene-divinylbenzene sulfonic acid type cation exchange resin.

[0030] Furthermore, the pH of the silicate solution after passing through the acidic ion exchange resin is 2-3.

[0031] Furthermore, the sintering heat treatment process includes: heating the raw material of the ceramsite proppant to 300°C~400°C at a rate of 3°C / min~5°C / min, and keeping it warm for 25~35 minutes; then heating it to 1150°C~1250°C at a rate of 3°C / min~5°C / min, and keeping it warm for 1.5~2.5 hours; finally cooling it to 20~35°C at a rate of 5°C / min~10°C / min to obtain a coal-based solid waste ceramsite proppant.

[0032] Furthermore, the coal gangue and fly ash acid slag in step S2 are crushed and ground to obtain respective powders, and the particle size of the powders is less than 200 meshes.

[0033] Furthermore, the mixing process of coal gangue, fly ash acid slag, sintering agent and binder includes: mixing powder of coal gangue, powder of fly ash acid slag and sintering agent to form mixed powder; and then spraying binder into the mixed powder.

[0034] Furthermore, the rotation speed of the granulator for granulation is 20 to 50 r / min.

[0035] Furthermore, the drying in step S3 is carried out in a blast drying oven at a drying temperature of 80°C to 120°C.

[0036] Furthermore, the mesh size of the sieving is 40 to 70 meshes.

[0037] The technical scheme of the present invention is applied to provide a coal-based solid waste ceramsite proppant and a preparation method thereof, which uses coal-based solid waste as the main raw material, completely replacing the use of high-aluminum raw materials, and reducing the production cost of the ceramsite proppant; the carbon content of the coal gangue used is ≥30%, which can be discharged in the form of gas during the roasting process to generate pores, thereby achieving the effect of reducing the density of the proppant, without the need to add additional pore-forming agents; the fly ash acid slag selected by the present invention has a high content of silicon dioxide, which can further improve the strength of the ceramsite proppant; the binder of the present invention adopts a mixture of homemade silicon dioxide hydrogel and polyethylene glycol or polyvinyl alcohol, and the silica sol colloidal particles have a small particle size and have a relatively Large specific surface area, good dispersion and permeability. On the one hand, silica is wrapped on the surface of the ceramsite proppant, and when the water of the binder evaporates, the colloidal particles firmly adhere to the surface of the object, which has good adhesion, can improve the mechanical properties of the material, and reduce the acid solubility; on the other hand, the silica hydrogel itself has a certain viscosity. After mixing with polyethylene glycol or polyvinyl alcohol, compared with the use of a single binder, the amount of binder is greatly reduced, and the production cost is reduced; the coal-based solid waste ceramsite proppant prepared by the present invention has the advantages of low density and high strength, and its crushing rate under 35MPa is 4% to 5.3%, and the crushing rate under 52MPa is 5% to 7.4%. DETAILED DESCRIPTION

[0038] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention is described in detail below with reference to embodiments.

[0039] The present invention uses solid waste coal gangue as a main raw material to prepare a coal-based solid waste ceramsite proppant, which includes a first raw material and a second raw material;

[0040] In terms of mass percentage, the first raw material includes: 60% to 75% of coal gangue, 25% to 40% of fly ash acid slag, and a total of 100%;

[0041] The second raw material includes: a sintering aid and a binder; the mass of the sintering aid is 0.5% to 2.5% of the total mass of the first raw material, and the mass of the binder is 8% to 10% of the total mass of the first raw material;

[0042] The binder is a mixture of polyethylene glycol or polyvinyl alcohol and silicon dioxide hydrogel.

[0043] The proportion of coal gangue in the first raw material of the present invention is selected from any value among 60%, 63%, 65%, 68%, 70%, 72%, 75% or any range between two values; the proportion of fly ash acid slag is selected from any value among 25%, 28%, 30%, 32%, 35%, 37%, 40% or any range between two values.

[0044] The proportion of the sintering aid in the second raw material of the present invention to the total mass of the first raw material is selected from any value selected from 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5% or any range between two values; the proportion of the binder to the total mass of the first raw material is selected from any value selected from 8%, 8.5%, 9%, 9.5%, 10% or any range between two values.

[0045] The present invention selects coal-based solid waste gangue as the main raw material, completely replacing the use of high-aluminum raw materials and reducing the production cost of ceramsite proppants; the carbon content in the gangue used is ≥30%, which can be discharged in the form of gas during the roasting process to generate pores, thereby achieving the effect of reducing the density of the proppant without the need to add additional pore-forming agents.

[0046] The fly ash acid slag selected in the present invention has a high content of silicon dioxide, which can further improve the strength of the ceramsite proppant. The fly ash acid slag is the tailings obtained after extracting alumina from fly ash as recorded in patent CN201110103722.6.

[0047] The binder selected in the present invention is a mixture of homemade silica hydrogel and polyethylene glycol or polyvinyl alcohol. The silica sol colloidal particles have a small particle size, a large specific surface area, and good dispersion permeability. On the one hand, silica is wrapped on the surface of the ceramsite proppant, and when the water of the binder evaporates, the colloidal particles firmly adhere to the surface of the object, have good adhesion, can improve the mechanical properties of the material, and reduce acid solubility at the same time; on the other hand, the silica hydrogel itself has a certain viscosity. After being mixed with polyethylene glycol or polyvinyl alcohol, compared with the use of a single binder, the amount of binder used is greatly reduced, thereby reducing the production cost.

[0048] The present invention adopts coal gangue as the main raw material, fly ash acid slag, a specific binder and a matching ratio of each raw material to obtain a coal-based solid waste ceramsite proppant with the advantages of low density and high strength. The volume density of the coal-based solid waste ceramsite proppant is 1.25-1.46 g / cm 3 , apparent density is 1.8~2.3g / cm 3 The crushing rate at 35MPa is 4% to 6%, the crushing rate at 52MPa is 5% to 8%, the sphericity is 0.7 to 0.9, and the acid solubility is 5% to 5.3%.

[0049] As a preferred embodiment, the mass percentage of coal gangue in the first raw material is 65% to 75%, and the mass percentage of fly ash acid slag is 25% to 35%; more preferably, the mass percentage of coal gangue in the first raw material is 68% to 70%, and the mass percentage of fly ash acid slag is 30% to 32%; the mass of the sintering aid is 0.5% to 2% of the total mass of the first raw material, and the mass of the binder is 9% to 10% of the total mass of the first raw material.

[0050] The coal gangue, fly ash acid slag, sintering aid and bonding agent of the present invention adopt the above-mentioned proportion, and the ceramsite proppant obtained has higher strength, lower acid solubility and lower density; the volume density of the coal-based solid waste ceramsite proppant is 1.25-1.4 g / cm 3 , apparent density is 1.8~2.1g / cm 3 The crushing rate at 35MPa is 4% to 5.3%, the crushing rate at 52MPa is 5% to 7.4%, the sphericity is 0.8 to 0.9, and the acid solubility is 5% to 5.28%.

[0051] The acid solubility in the present invention refers to the percentage of a certain mass of proppant dissolved by the acid solution to the total mass of the proppant under specified acid solution and reaction conditions.

[0052] As a specific implementation manner, the mass of polyethylene glycol or polyvinyl alcohol in the binder accounts for 3% to 5% of the total mass of the mixed solution, and the remainder is silica hydrogel, which is 100% in total.

[0053] The silica sol colloidal particles in the self-made binder of the present invention have a small particle size, a large specific surface area, and good dispersion and permeability. The silica is wrapped on the surface of the ceramsite proppant. When the water content of the binder evaporates, the colloidal particles firmly adhere to the surface of the object, have good adhesion, can improve the mechanical properties of the material, and reduce the acid solubility at the same time. The silica hydrogel itself has a certain viscosity. After being mixed with polyethylene glycol or polyvinyl alcohol, compared with the use of a single binder, the amount of the binder is greatly reduced, thereby reducing the production cost.

[0054] As a specific implementation manner, the raw material of the silica hydrogel is fly ash acid slag.

[0055] The fly ash acid slag selected as the binder of the present invention has a high content of silicon dioxide, which can further improve the strength of the expanded clay proppant; wherein, the fly ash acid slag is the tailings obtained after extracting alumina from fly ash as recorded in patent CN201110103722.6; the binder of the present invention makes full use of the solid waste material fly ash acid slag, greatly reducing the raw material cost.

[0056] As a specific implementation, the particle size of the silica hydrogel in the binder is 10 to 20 nm.

[0057] The present invention selects the above-mentioned silica sol colloidal particles with smaller particle size, which have a larger specific surface area and good dispersion permeability. On the one hand, silicon dioxide is wrapped on the surface of the ceramsite proppant, and when the water of the adhesive evaporates, the colloidal particles are firmly adhered to the surface of the object, having good adhesion, which can improve the mechanical properties of the material and reduce the acid solubility.

[0058] As a specific implementation, the sintering aid is calcium oxide or magnesium oxide.

[0059] The present invention selects the above-mentioned sintering aid to promote the subsequent sintering process, stabilize the sintering process, etc.

[0060] As a specific implementation method, the main phase component of the coal-based solid waste ceramsite proppant is mullite phase; the proppant material having this phase has the advantages of high hardness, high temperature resistance, wear resistance, acid and alkali corrosion resistance, etc.

[0061] According to a second aspect of the present invention, a method for preparing the above-mentioned coal-based solid waste ceramsite proppant is provided, comprising the following steps:

[0062] Step S1: Obtaining various raw materials according to the recipe;

[0063] Step S2: mixing and granulating coal gangue, fly ash acid slag, sintering aid and binder to obtain a spherical green body;

[0064] Step S3: drying and sieving the spherical green bodies to obtain ceramsite proppant raw materials;

[0065] Step S4: The ceramsite proppant raw material is sintered to obtain a coal-based solid waste ceramsite proppant.

[0066] The ceramsite proppant prepared by the preparation method of the present invention has the advantages of low density and high strength, and the method is simple to operate and low in cost.

[0067] As a specific implementation, the preparation method of the binder comprises the following steps:

[0068] Step S2-1: adding water to the fly ash acid slag for 3 to 5 times, stirring and washing, and adjusting the pH value of the fly ash acid slag solution to 8 to 9 with an alkaline solution to obtain a silicate solution; the sodium silicate solution is passed through an acidic ion exchange resin and then adjusted to a pH value of 5 to 6 with ammonia water to obtain a silica hydrogel;

[0069] The hydrogel prepared by the present invention has a small particle size, a large specific surface area, and good bonding performance. When mixed with other materials, the silicon dioxide is wrapped on the surface of the ceramsite proppant, and the colloidal particles are firmly adhered to the surface of the object when the water of the adhesive evaporates, and has good bonding properties, which can improve the mechanical properties of the material and reduce the acid solubility.

[0070] Step S2-2: Add polyethylene glycol or polyvinyl alcohol to the silica hydrogel in proportion to obtain a binder.

[0071] The method adopted by the present invention is simple to operate, fully utilizes the solid waste fly ash acid slag, greatly reduces the production cost, and the obtained binder has good bonding performance, reduces the usage of other binders, and further reduces the production cost.

[0072] As a specific implementation, the alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution.

[0073] As a specific implementation, the acidic ion exchange resin includes polystyrene sulfonic acid type ion exchange resin and polystyrene-divinylbenzene sulfonic acid type cation exchange resin; the pH of the sodium silicate solution after passing through the acidic ion exchange resin is 2-3.

[0074] The present invention adopts the above method to first adjust the pH of fly ash acid slag to alkalinity, then perform ion exchange through strong acid ion exchange resin under alkaline conditions, and adjust the pH to weak acidity, so as to successfully obtain silica hydrogel, which is convenient to use.

[0075] As a specific implementation method, the sintering heat treatment process includes: heating the raw material of the ceramsite proppant to 300°C~400°C at a rate of 3°C / min~5°C / min, and keeping it warm for 25~35min; then heating it to 1150~1250°C at a rate of 3°C / min~5°C / min, and keeping it warm for 1.5~2.5h; finally cooling it to 20~35°C at a rate of 5°C / min~10°C / min to obtain a coal-based solid waste ceramsite proppant.

[0076] The present invention adopts the above sintering conditions to preferably sinter the spherical raw material into a ceramsite proppant with ideal hardness or strength and low density.

[0077] As a specific implementation manner, the coal gangue and fly ash acid slag in step S2 are crushed and ground to obtain respective powders, and the particle size of the powders is less than 200 meshes.

[0078] The present invention uses powder with the above-mentioned particle size, which is conducive to forming spherical particles with uniform components and helps to have uniform strength and density after sintering.

[0079] As a specific implementation method, the mixing process of coal gangue, fly ash acid slag, sintering agent and binder includes: mixing powder of coal gangue, powder of fly ash acid slag and sintering agent to form a mixed powder; spraying the binder into the mixed powder; the granulator speed of granulation is 20 to 50 r / min; the drying in step S3 is in a blast drying oven, and the drying temperature is 80°C to 120°C; the mesh size of the sieving is 40 to 70 meshes.

[0080] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0081] Example 1

[0082] (1) crushing and grinding coal gangue and fly ash acid slag respectively until the particle size is smaller than the sieve hole size of a 200-mesh standard sieve, and the 200-mesh sieve residue is 33.83%, thereby obtaining an initial powder;

[0083] (2) adding water to the fly ash acid slag for three times, stirring and washing, adjusting the pH to 8 with sodium hydroxide solution to obtain a sodium silicate solution, using polystyrene sulfonic acid type ion exchange resin to obtain a silicic acid solution with a pH of 2, and adjusting the pH to 5 with ammonia water to obtain a silica hydrogel; then adding polyethylene glycol accounting for 3% of the total amount of the binder mixture to obtain a self-made binder for later use;

[0084] (3) 65% of coal gangue powder and 35% of fly ash acid slag are weighed as main raw materials, and then calcium oxide accounting for 2.5% of the weight of the main raw materials is added as a flux, and mechanically mixed for 15 minutes to obtain a mixture;

[0085] (4) The mixed material obtained in step (3) is transferred into a granulator, the speed is set to 50 r / min, and the homemade binder is evenly sprayed on the mixed powder using a spray pot. After granulation for 15 minutes, the speed is adjusted to 35 r / min, and granulation is continued. When the mixed powder is basically balled, granulation is stopped; the mass of the homemade binder used accounts for 9% of the main raw materials;

[0086] (5) Screening the ball material obtained in step (4) to obtain small balls of 40-70 mesh, and then drying them in a forced air drying oven at 80° C. to obtain a raw material of coal-based solid waste-based ceramsite proppant;

[0087] (6) placing the ceramsite proppant raw material obtained in step (5) in a muffle furnace, heating it to 350° C. at a rate of 3° C. / min, keeping it warm for 30 min, and then slowly heating it to 1150° C., keeping it warm for 2.5 h, and sintering it into a coal-based solid waste ceramsite proppant finished product;

[0088] (7) Cooling the ceramsite proppant obtained in step (6) to room temperature at a rate of 5° C. / min to obtain a ceramsite proppant.

[0089] Example 2

[0090] (1) crushing and grinding coal gangue and fly ash acid slag respectively to a particle size smaller than the sieve size of a 200-mesh standard sieve, with a 200-mesh sieve residue of 33.83%, to obtain an initial powder;

[0091] (2) adding water to the fly ash acid slag for 5 times, stirring and washing, adjusting the pH to 9 with potassium hydroxide to obtain a potassium silicate solution, passing a polystyrene-divinylbenzenesulfonic acid type cation exchange resin to obtain a silica solution with a pH of 2.5, and adjusting the pH to 5 with ammonia water to obtain a silica hydrogel; then adding polyvinyl alcohol accounting for 4% of the total amount of the binder mixture to obtain a self-made binder for later use;

[0092] (3) 70% of coal gangue powder and 30% of fly ash acid slag are weighed as main raw materials, and then 0.5% of calcium oxide by weight of the main raw materials is added as a flux, and mechanically mixed for 25 minutes to obtain a mixture;

[0093] (4) The mixed material obtained in step (3) is transferred into a granulator, the speed is set to 50 r / min, and the homemade binder is evenly sprayed on the mixed powder using a spray pot. After granulation for 15 minutes, the speed is adjusted to 30 r / min, and granulation is continued. When the mixed powder is basically formed into balls, granulation is stopped; the mass of the homemade binder used accounts for 8% of the main raw materials;

[0094] (5) Screening the ball material obtained in step (4) to obtain small balls of 40-70 mesh, and then drying them in a forced air drying oven at 80° C. to obtain a raw material of coal-based solid waste-based ceramsite proppant;

[0095] (6) placing the ceramsite proppant raw material obtained in step (5) in a muffle furnace, heating it to 400° C. at 5° C. / min, keeping it warm for 30 min, and then slowly heating it to 1250° C., keeping it warm for 1.5 h, and sintering it into a coal-based solid waste ceramsite proppant finished product;

[0096] (7) Cooling the ceramsite proppant obtained in step (6) to room temperature at a rate of 10° C. / min to obtain a ceramsite proppant.

[0097] Example 3

[0098] (1) crushing and grinding coal gangue and fly ash acid slag respectively to a particle size smaller than the sieve size of a 200-mesh standard sieve, with a 200-mesh sieve residue of 33.83%, to obtain an initial powder;

[0099] (2) adding water to the fly ash acid slag for 4 times, stirring and washing, adjusting the pH to 8.5 with sodium hydroxide solution to obtain a sodium silicate solution, using polystyrene sulfonic acid type ion exchange resin to obtain a silicic acid solution with a pH of 3, and adjusting the pH to 5.5 with ammonia water to obtain a silica hydrogel; then adding polyvinyl alcohol accounting for 5% of the total amount of the mixed solution to obtain a self-made binder for later use;

[0100] (3) 68% of coal gangue powder and 32% of fly ash acid slag were weighed as main raw materials, and then 2% of magnesium oxide as a flux was added thereto by weight of the main raw materials, and mechanically mixed for 20 minutes to obtain a mixture;

[0101] (4) The mixed material obtained in step (3) is transferred to a granulator, the speed is set to 40 r / min, and the homemade binder is evenly sprayed on the mixed powder using a spray pot. After granulation for 15 minutes, the speed is adjusted to 20 r / min, and granulation is continued. When the mixed powder is basically formed into balls, granulation is stopped; the mass of the homemade binder used accounts for 10% of the main raw materials;

[0102] (5) Screening the ball material obtained in step (4) to obtain small balls of 40-70 mesh, and then drying them in a forced air drying oven at 120° C. to obtain a raw material of coal-based solid waste-based ceramsite proppant;

[0103] (6) placing the ceramsite proppant raw material obtained in step (5) in a muffle furnace, heating it to 400° C. at 5° C. / min, keeping it warm for 20 min, and then slowly heating it to 1150° C., keeping it warm for 2.5 h, and sintering it into a coal-based solid waste ceramsite proppant finished product;

[0104] (7) Cooling the ceramsite proppant obtained in step (6) to room temperature at a rate of 6° C. / min to obtain a ceramsite proppant.

[0105] Example 4

[0106] (1) crushing and grinding coal gangue and fly ash acid slag respectively to a particle size smaller than the sieve size of a 200-mesh standard sieve, with a 200-mesh sieve residue of 33.83%, to obtain an initial powder;

[0107] (2) adding water to the fly ash acid slag for 4 times, stirring and washing, adjusting the pH to 9 with potassium hydroxide solution to obtain a potassium silicate solution, passing through a polystyrene-divinylbenzenesulfonic acid type cation exchange resin to obtain a silica solution with a pH of 2.5, and adjusting the pH to 6 with ammonia water to obtain a silica hydrogel; then adding polyethylene glycol accounting for 5% of the total amount of the mixed solution to obtain a self-made binder for later use;

[0108] (3) 70% of coal gangue powder and 30% of fly ash acid slag were weighed as main raw materials, and then 1.5% of magnesium oxide as a flux was added thereto by weight of the main raw materials, and mechanically mixed for 18 minutes to obtain a mixture;

[0109] (4) The mixed material obtained in step (3) is transferred into a granulator, the speed is set to 50 r / min, and the homemade binder is evenly sprayed on the mixed powder using a spray pot. After granulation for 15 minutes, the speed is adjusted to 20 r / min, and granulation is continued. When the mixed powder is basically balled, granulation is stopped; the mass of the homemade binder used accounts for 10% of the main raw materials;

[0110] (5) Screening the ball material obtained in step (4) to obtain small balls of 40-70 mesh, and then drying them in a forced air drying oven at 120° C. to obtain a raw material of coal-based solid waste-based ceramsite proppant;

[0111] (6) placing the ceramsite proppant raw material obtained in step (5) in a muffle furnace, heating it to 300° C. at a rate of 3° C. / min, keeping it warm for 30 min, and then slowly heating it to 1200° C., keeping it warm for 1.5 h, and sintering it into a coal-based solid waste ceramsite proppant finished product;

[0112] (7) Cooling the ceramsite proppant obtained in step (6) to room temperature at a rate of 9° C. / min to obtain a ceramsite proppant.

[0113] Example 5

[0114] (1) crushing and grinding coal gangue and fly ash acid slag respectively to a particle size smaller than the sieve size of a 200-mesh standard sieve, with a 200-mesh sieve residue of 33.83%, to obtain an initial powder;

[0115] (2) adding water to the fly ash acid slag for 4 times, stirring and washing, adjusting the pH to 9 with sodium hydroxide solution to obtain a sodium silicate solution, using polystyrene sulfonic acid type ion exchange resin to obtain a silicic acid solution with a pH of 2.5, and adjusting the pH to 6 with ammonia water to obtain a silica hydrogel; then adding polyethylene glycol accounting for 5% of the total amount of the mixed solution to obtain a self-made binder for later use;

[0116] (3) 75% of coal gangue powder and 25% of fly ash acid slag were weighed as main raw materials, and then 1.8% of magnesium oxide as a flux was added thereto by weight of the main raw materials, and mechanically mixed for 18 minutes to obtain a mixture;

[0117] (4) The mixed material obtained in step (3) is transferred into a granulator, the speed is set to 50 r / min, and the homemade binder is evenly sprayed on the mixed powder using a spray pot. After granulation for 15 minutes, the speed is adjusted to 20 r / min, and granulation is continued. When the mixed powder is basically balled, granulation is stopped; the mass of the homemade binder used accounts for 10% of the main raw materials;

[0118] (5) Screening the ball material obtained in step (4) to obtain small balls of 40-70 mesh, and then drying them in a forced air drying oven at 120° C. to obtain a raw material of coal-based solid waste-based ceramsite proppant;

[0119] (6) placing the ceramsite proppant raw material obtained in step (5) in a muffle furnace, heating it to 400° C. at 3° C. / min, keeping it warm for 30 min, and then slowly heating it to 1250° C., keeping it warm for 1.5 h, and sintering it into a coal-based solid waste ceramsite proppant finished product;

[0120] (7) Cooling the ceramsite proppant obtained in step (6) to room temperature at a rate of 10° C. / min to obtain a ceramsite proppant.

[0121] Example 6

[0122] The difference between Example 6 and Example 3 is that the sintering conditions of step (6) are: heating to 1290° C. at 3° C. / min and keeping the temperature for 2.5 h.

[0123] (1) crushing and grinding coal gangue and fly ash acid slag respectively to a particle size smaller than the sieve size of a 200-mesh standard sieve, with a 200-mesh sieve residue of 33.83%, to obtain an initial powder;

[0124] (2) adding water to the fly ash acid slag for 4 times, stirring and washing, adjusting the pH to 8.5 with sodium hydroxide solution to obtain a sodium silicate solution, using polystyrene sulfonic acid type ion exchange resin to obtain a silicic acid solution with a pH of 3, and adjusting the pH to 5.5 with ammonia water to obtain a silica hydrogel; then adding polyvinyl alcohol accounting for 5% of the total amount of the mixed solution to obtain a self-made binder for later use;

[0125] (3) 68% of coal gangue powder and 32% of fly ash acid slag were weighed as main raw materials, and then 2% of magnesium oxide as a flux was added thereto by weight of the main raw materials, and mechanically mixed for 20 minutes to obtain a mixture;

[0126] (4) The mixed material obtained in step (3) is transferred to a granulator, the speed is set to 40 r / min, and the homemade binder is evenly sprayed on the mixed powder using a spray pot. After granulation for 15 minutes, the speed is adjusted to 20 r / min, and granulation is continued. When the mixed powder is basically formed into balls, granulation is stopped; the mass of the homemade binder used accounts for 10% of the main raw materials;

[0127] (5) Screening the ball material obtained in step (4) to obtain small balls of 40-70 mesh, and then drying them in a forced air drying oven at 120° C. to obtain a raw material of coal-based solid waste-based ceramsite proppant;

[0128] (6) placing the ceramsite proppant raw material obtained in step (5) in a muffle furnace, heating it to 1290° C. at a rate of 3° C. / min, keeping it at that temperature for 2.5 h, and sintering it into a coal-based solid waste ceramsite proppant finished product;

[0129] (7) Cooling the ceramsite proppant obtained in step (6) to room temperature at a rate of 6° C. / min to obtain a ceramsite proppant.

[0130] Comparative Example 1

[0131] The difference between Comparative Example 1 and Example 3 is that there is no step (2), and in step (4), a sodium carboxymethyl cellulose aqueous solution is added as a binder. The specific steps are as follows:

[0132] (1) crushing and grinding coal gangue and fly ash acid slag respectively to a particle size smaller than the sieve size of a 200-mesh standard sieve, with a 200-mesh sieve residue of 33.83%, to obtain an initial powder;

[0133] (2) 68% of coal gangue powder and 32% of fly ash acid slag are weighed as main raw materials, and then 2% of magnesium oxide as a flux is added thereto, and mechanically mixed for 20 minutes to obtain a mixture;

[0134] (3) The mixed material obtained in step (2) is transferred to a granulator, the speed is set to 40 r / min, and the sodium carboxymethyl cellulose aqueous solution binder is evenly sprayed on the mixed powder using a spray pot. After granulation for 15 minutes, the speed is adjusted to 20 r / min, and granulation is continued. When the mixed powder is basically balled, granulation is stopped; wherein the mass of the binder used accounts for 10% of the main raw material;

[0135] (4) screening the ball material obtained in step (3) to obtain small balls of 40-70 mesh, and then drying them in a forced air drying oven at 120° C. to obtain a raw material of coal-based solid waste-based ceramsite proppant;

[0136] (5) placing the ceramsite proppant raw material obtained in step (4) in a muffle furnace, heating it to 400° C. at 5° C. / min, keeping it warm for 20 min, and then slowly heating it to 1150° C., keeping it warm for 2.5 h, and sintering it into a coal-based solid waste ceramsite proppant finished product;

[0137] (6) Cooling the ceramsite proppant obtained in step (5) to room temperature at a rate of 6° C. / min to obtain a ceramsite proppant.

[0138] Comparative Example 2

[0139] The difference between Comparative Example 2 and Example 3 is that the fly ash acid slag in step (3) is replaced by fly ash; the specific steps are as follows:

[0140] (1) crushing and grinding coal gangue and fly ash acid slag respectively to a particle size smaller than the sieve size of a 200-mesh standard sieve, with a 200-mesh sieve residue of 33.83%, to obtain an initial powder;

[0141] (2) adding water to the fly ash acid slag for 4 times, stirring and washing, adjusting the pH to 8.5 with sodium hydroxide solution to obtain a sodium silicate solution, using polystyrene sulfonic acid type ion exchange resin to obtain a silicic acid solution with a pH of 3, and adjusting the pH to 5.5 with ammonia water to obtain a silica hydrogel; then adding polyvinyl alcohol accounting for 5% of the total amount of the mixed solution to obtain a self-made binder for later use;

[0142] (3) Weighing 68% of coal gangue powder and 32% of fly ash as main raw materials, adding 2% of magnesium oxide as a flux, and mechanically mixing for 20 minutes to obtain a mixture;

[0143] (4) The mixed material obtained in step (3) is transferred to a granulator, the speed is set to 40 r / min, and the homemade binder is evenly sprayed on the mixed powder using a spray pot. After granulation for 15 minutes, the speed is adjusted to 20 r / min, and granulation is continued. When the mixed powder is basically formed into balls, granulation is stopped; the mass of the homemade binder used accounts for 10% of the main raw materials;

[0144] (5) Screening the ball material obtained in step (4) to obtain small balls of 40-70 mesh, and then drying them in a forced air drying oven at 120° C. to obtain a raw material of coal-based solid waste-based ceramsite proppant;

[0145] (6) placing the ceramsite proppant raw material obtained in step (5) in a muffle furnace, heating it to 400° C. at 5° C. / min, keeping it warm for 20 min, and then slowly heating it to 1150° C., keeping it warm for 2.5 h, and sintering it into a coal-based solid waste ceramsite proppant finished product;

[0146] (7) Cooling the ceramsite proppant obtained in step (6) to room temperature at a rate of 6° C. / min to obtain a ceramsite proppant.

[0147] Comparative Example 3

[0148] The difference between Comparative Example 3 and Example 3 is that the mass percentage of the gangue powder in step (3) is 55%, and the mass percentage of the fly ash acid slag is 45%; the specific steps are as follows:

[0149] (1) crushing and grinding coal gangue and fly ash acid slag respectively to a particle size smaller than the sieve size of a 200-mesh standard sieve, with a 200-mesh sieve residue of 33.83%, to obtain an initial powder;

[0150] (2) adding water to the fly ash acid slag for 4 times, stirring and washing, adjusting the pH to 8.5 with sodium hydroxide solution to obtain a sodium silicate solution, using polystyrene sulfonic acid type ion exchange resin to obtain a silicic acid solution with a pH of 3, and adjusting the pH to 5.5 with ammonia water to obtain a silica hydrogel; then adding polyvinyl alcohol accounting for 5% of the total amount of the mixed solution to obtain a self-made binder for later use;

[0151] (3) 55% of coal gangue powder and 45% of fly ash acid slag are weighed as main raw materials, and then 2% of magnesium oxide as a flux is added thereto, and mechanically mixed for 20 minutes to obtain a mixture;

[0152] (4) The mixed material obtained in step (3) is transferred to a granulator, the speed is set to 40 r / min, and the homemade binder is evenly sprayed on the mixed powder using a spray pot. After granulation for 15 minutes, the speed is adjusted to 20 r / min, and granulation is continued. When the mixed powder is basically formed into balls, granulation is stopped; the mass of the homemade binder used accounts for 10% of the main raw materials;

[0153] (5) Screening the ball material obtained in step (4) to obtain small balls of 40-70 mesh, and then drying them in a forced air drying oven at 120° C. to obtain a raw material of coal-based solid waste-based ceramsite proppant;

[0154] (6) placing the ceramsite proppant raw material obtained in step (5) in a muffle furnace, heating it to 400° C. at 5° C. / min, keeping it warm for 20 min, and then slowly heating it to 1150° C., keeping it warm for 2.5 h, and sintering it into a coal-based solid waste ceramsite proppant finished product;

[0155] (7) Cooling the ceramsite proppant obtained in step (6) to room temperature at a rate of 6° C. / min to obtain a ceramsite proppant.

[0156] Comparative Example 4

[0157] The difference between Comparative Example 4 and Example 3 is that the amount of binder used in step (4) is 5% of the total amount of the main raw materials.

[0158] (1) crushing and grinding coal gangue and fly ash acid slag respectively to a particle size smaller than the sieve size of a 200-mesh standard sieve, with a 200-mesh sieve residue of 33.83%, to obtain an initial powder;

[0159] (2) adding water to the fly ash acid slag for 4 times, stirring and washing, adjusting the pH to 8.5 with sodium hydroxide solution to obtain a sodium silicate solution, using polystyrene sulfonic acid type ion exchange resin to obtain a silicic acid solution with a pH of 3, and adjusting the pH to 5.5 with ammonia water to obtain a silica hydrogel; then adding polyvinyl alcohol accounting for 5% of the total amount of the mixed solution to obtain a self-made binder for later use;

[0160] (3) 68% of coal gangue powder and 32% of fly ash acid slag were weighed as main raw materials, and then 2% of magnesium oxide as a flux was added thereto by weight of the main raw materials, and mechanically mixed for 20 minutes to obtain a mixture;

[0161] (4) The mixed material obtained in step (3) is transferred into a granulator, the speed is set to 40 r / min, and the homemade binder is evenly sprayed on the mixed powder using a spray pot. After granulation for 15 minutes, the speed is adjusted to 20 r / min, and granulation is continued. When the mixed powder is basically balled, granulation is stopped; the mass of the homemade binder used accounts for 5% of the main raw materials;

[0162] (5) Screening the ball material obtained in step (4) to obtain small balls of 40-70 mesh, and then drying them in a forced air drying oven at 120° C. to obtain a raw material of coal-based solid waste-based ceramsite proppant;

[0163] (6) placing the ceramsite proppant raw material obtained in step (5) in a muffle furnace, heating it to 400° C. at 5° C. / min, keeping it warm for 20 min, and then slowly heating it to 1150° C., keeping it warm for 2.5 h, and sintering it into a coal-based solid waste ceramsite proppant finished product;

[0164] (7) Cooling the ceramsite proppant obtained in step (6) to room temperature at a rate of 6° C. / min to obtain a ceramsite proppant.

[0165] Comparative Example 5

[0166] The difference between Comparative Example 5 and Example 3 is that the amount of binder used in step (4) is 15% of the total amount of the main raw materials; the specific steps are as follows:

[0167] (1) crushing and grinding coal gangue and fly ash acid slag respectively to a particle size smaller than the sieve size of a 200-mesh standard sieve, with a 200-mesh sieve residue of 33.83%, to obtain an initial powder;

[0168] (2) adding water to the fly ash acid slag for 4 times, stirring and washing, adjusting the pH to 8.5 with sodium hydroxide solution to obtain a sodium silicate solution, using polystyrene sulfonic acid type ion exchange resin to obtain a silicic acid solution with a pH of 3, and adjusting the pH to 5.5 with ammonia water to obtain a silica hydrogel; then adding polyvinyl alcohol accounting for 5% of the total amount of the mixed solution to obtain a self-made binder for later use;

[0169] (3) 68% of coal gangue powder and 32% of fly ash acid slag were weighed as main raw materials, and then 2% of magnesium oxide as a flux was added thereto by weight of the main raw materials, and mechanically mixed for 20 minutes to obtain a mixture;

[0170] (4) The mixed material obtained in step (3) is transferred to a granulator, the speed is set to 40 r / min, and the homemade binder is evenly sprayed on the mixed powder using a spray pot. After granulation for 15 minutes, the speed is adjusted to 20 r / min, and granulation is continued. When the mixed powder is basically formed into balls, granulation is stopped; the mass of the homemade binder used accounts for 15% of the main raw materials;

[0171] (5) Screening the ball material obtained in step (4) to obtain small balls of 40-70 mesh, and then drying them in a forced air drying oven at 120° C. to obtain a raw material of coal-based solid waste-based ceramsite proppant;

[0172] (6) placing the ceramsite proppant raw material obtained in step (5) in a muffle furnace, heating it to 400° C. at 5° C. / min, keeping it warm for 20 min, and then slowly heating it to 1150° C., keeping it warm for 2.5 h, and sintering it into a coal-based solid waste ceramsite proppant finished product;

[0173] (7) Cooling the ceramsite proppant obtained in step (6) to room temperature at a rate of 6° C. / min to obtain a ceramsite proppant.

[0174] The main components of the coal gangue selected in the embodiment of the present invention are shown in Table 1, the main components of the fly ash acid slag selected are shown in Table 2, and the main components of the fly ash used in Comparative Example 2 are shown in Table 3.

[0175] The bulk density, apparent density, sphericity, acid solubility and crushing rate of the coal-based solid waste ceramsite proppants prepared in Examples 1 to 5 and Comparative Examples 1 to 6 were tested according to standard SY / T 5108-2014. The experimental results are shown in Table 4.

[0176] Table 1 Main components of coal gangue

[0177] Element <![CDATA[SiO2]]> <![CDATA[Al2O3]]> CaO <![CDATA[Fe2O3]]> <![CDATA[TiO2]]> <![CDATA[K2O]]> LOI Mass content / % 32.02 31.32 0.31 0.54 0.77 0.23 34.68

[0178] Table 2 Main components of fly ash acid slag

[0179] Element <![CDATA[SiO2]]> <![CDATA[Al2O3]]> CaO <![CDATA[Fe2O3]]> <![CDATA[TiO2]]> <![CDATA[K2O]]> LOI Mass content / % 70.28 16.34 0.18 0.40 2.99 0.16 6.56

[0180] Table 3 Main components of fly ash

[0181] Element <![CDATA[SiO2]]> <![CDATA[Al2O3]]> CaO <![CDATA[Fe2O3]]> <![CDATA[TiO2]]> <![CDATA[K2O]]> LOI Mass content / % 35.30 51.08 3.14 2.07 1.84 0.30 4.30

[0182] Table 4 Performance test results of coal-based solid waste ceramsite proppants of Examples 1 to 5 and Comparative Examples 1 to 6

[0183]

[0184] In Examples 1 to 6 of the present invention, by using coal gangue as the main raw material, fly ash acid slag, a specific binder and a matching ratio of each raw material, the coal-based solid waste ceramsite proppant obtained has the advantages of low density and high strength. The volume density of the coal-based solid waste ceramsite proppant is 1.25 to 1.46 g / cm 3 , apparent density is 1.86~2.30g / cm 3, the crushing rate at 35MPa is 4% to 5.93%, the crushing rate at 52MPa is 5.2% to 7.91%, the sphericity is 0.8, and the acid solubility is 5% to 5.28%. Among them, by further optimizing the raw material formula, the ceramsite proppant prepared in Examples 1 to 5 has higher strength, lower acid solubility and lower density, and the bulk density is preferably 1.25 to 1.39 g / cm 3 , apparent density is 1.8~2.3g / cm 3 , the crushing rate at 35MPa is 4% to 5.21%, the crushing rate at 52MPa is 5% to 7.32%, the sphericity is 0.8, and the acid solubility is 5% to 5.28%. Example 6 adopts a one-step sintering process, and the ceramsite proppant prepared therefrom also achieves the characteristics of lower density and slightly higher strength required by the present invention, but the overall characteristics are not as good as the two-step heating process adopted in Examples 1 to 5.

[0185] The binder used in Comparative Example 1 is a common binder sodium carboxymethyl cellulose aqueous solvent, and the ceramsite proppant prepared therefrom has increased density, decreased strength, and increased breakage rate.

[0186] Comparative Example 2 uses fly ash and coal gangue as main raw materials. The silica content in fly ash is relatively low. The prepared ceramsite proppant has increased density, reduced strength, and significantly higher crushing rate at 52 MPa.

[0187] When the ratio of the coal gangue powder and the fly ash acid slag in Comparative Example 3 is not matched, the synergistic effect is relatively small, and the density and the crushing rate of the prepared ceramsite proppant at 52 MPa are significantly higher.

[0188] In the ceramsite proppants prepared in Comparative Examples 4 and 5, too little binder content leads to increased acid solubility and reduced strength of the proppant; too much binder content leads to increased density of the proppant.

[0189] By comparing Examples 1 to 6 and Comparative Examples 1 to 5, it can be seen that the present invention selects fly ash acid slag and coal gangue containing a high silicon dioxide content, an appropriate ratio of the two, a special binder and its dosage, and a matching sintering process, and multiple factors work together to promote the improvement of the high strength and low density characteristics of the ceramsite proppant. At the same time, due to the different material selection, the production cost is also reduced.

[0190] The ceramsite proppant prepared by the present invention has the advantages of low cost, low density, high strength, etc. On the one hand, it completely replaces the use of high-aluminum raw materials such as bauxite, reducing the production cost of the ceramsite proppant, and on the other hand, it opens up a new way for the resource utilization of coal-based solid waste.

[0191] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

Claims

1. A coal-based solid waste ceramsite proppant, characterized in that: It includes a first raw material and a second raw material; In terms of mass percentage, the first raw material includes: 60% to 75% of coal gangue, 25% to 40% of fly ash acid slag, and a total of 100%; The second raw material includes: a sintering aid and a binder; the mass of the sintering aid is 0.5% to 2.5% of the total mass of the first raw material, and the mass of the binder is 8% to 10% of the total mass of the first raw material; The binder is a mixture of polyethylene glycol or polyvinyl alcohol and silicon dioxide hydrogel.

2. The coal-based solid waste ceramsite proppant according to claim 1, characterized in that: The mass percentage of the coal gangue in the first raw material is 65% to 75%, and the mass percentage of the fly ash acid slag is 25% to 35%; And / or, the mass of the sintering aid is 0.5% to 2% of the total mass of the first raw material, and the mass of the binder is 9% to 10% of the total mass of the first raw material.

3. The coal-based solid waste ceramsite proppant according to claim 1 or 2, characterized in that: The mass percentage of the coal gangue in the first raw material is 68% to 70%, and the mass percentage of the fly ash acid slag is 30% to 32%; And / or, the mass of the polyethylene glycol or the polyvinyl alcohol accounts for 3% to 5% of the total mass of the mixed solution, and the remainder is the silica hydrogel, which is 100% in total.

4. The coal-based solid waste ceramsite proppant according to any one of claims 1 to 3, characterized in that: The raw material of the silica hydrogel is fly ash acid slag; and / or, the particle size of the silica hydrogel is 10 to 20 nm; And / or, the sintering aid is calcium oxide or magnesium oxide; And / or, the main phase component of the coal-based solid waste ceramsite proppant is mullite phase; And / or, the volume density of the coal-based solid waste ceramsite proppant is 1.25-1.46 g / cm 3 , apparent density is 1.8~2.3g / cm 3 , the crushing rate at 35MPa is 4% to 6%, the crushing rate at 52MPa is 5% to 8%, the sphericity is 0.7 to 0.9, and the acid solubility is 5% to 5.3%; Preferably, the bulk density of the coal-based solid waste ceramsite proppant is 1.25-1.4 g / cm 3 , apparent density is 1.8~2.1g / cm 3 The crushing rate at 35MPa is 4% to 5.3%, the crushing rate at 52MPa is 5% to 7.4%, the sphericity is 0.8 to 0.9, and the acid solubility is 5% to 5.28%.

5. The method for preparing the coal-based solid waste ceramsite proppant according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: Step S1: Obtaining various raw materials according to the recipe; Step S2: mixing and granulating coal gangue, fly ash acid slag, sintering aid and binder to obtain a spherical green body; Step S3: drying and sieving the spherical green bodies to obtain ceramsite proppant raw materials; Step S4: The ceramsite proppant raw material is sintered to obtain the coal-based solid waste ceramsite proppant.

6. The method for preparing the coal-based solid waste ceramsite proppant according to claim 5, characterized in that: The preparation method of the binder comprises the following steps: Step S2-1: using an alkaline solution to adjust the pH value of the fly ash acid slag solution to 8-9 to obtain a silicate solution; the silicate solution is passed through an acidic ion exchange resin and then adjusted to a pH value of 5-6 using ammonia water to obtain the silica hydrogel; Step S2-2: adding polyethylene glycol or polyvinyl alcohol to the silica hydrogel in proportion to obtain the binder.

7. The method for preparing the coal-based solid waste ceramsite proppant according to claim 6, characterized in that: The alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution; And / or, the acidic ion exchange resin includes polystyrene sulfonic acid type ion exchange resin and polystyrene-divinylbenzene sulfonic acid type cation exchange resin; And / or, the pH of the silicate solution after passing through the acidic ion exchange resin is 2-3.

8. The method for preparing the coal-based solid waste ceramsite proppant according to any one of claims 5 to 7, characterized in that: The sintering heat treatment process includes: heating the raw material of the ceramsite proppant to 300-400°C at a rate of 3°C / min-5°C / min, and keeping it warm for 25-35 minutes; then heating it to 1150-1250°C at a rate of 3°C / min-5°C / min, and keeping it warm for 1.5-2.5 hours; finally cooling it to 20°C-35°C at a rate of 5°C / min-10°C / min to obtain the coal-based solid waste ceramsite proppant.

9. The method for preparing the coal-based solid waste ceramsite proppant according to any one of claims 5 to 8, characterized in that: The coal gangue and the fly ash acid slag in step S2 are crushed and ground to obtain respective powders, and the particle size of the powders is less than 200 meshes; And / or, the mixing process of the coal gangue, the fly ash acid slag, the sintering aid and the binder comprises: mixing the powder of the coal gangue, the powder of the fly ash acid slag and the sintering aid to form a mixed material powder; and then spraying the binder into the mixed material powder; And / or, the rotation speed of the granulator for granulation is 20 to 50 r / min.

10. The method for preparing the coal-based solid waste ceramsite proppant according to any one of claims 5 to 9, characterized in that: The drying in step S3 is carried out in a blast drying oven at a temperature of 80°C to 120°C; And / or, the mesh size of the sieving is 40 to 70 meshes.

Citation Information

Patent Citations

  • Method for dissolving aluminum out of circulating fluidized bed coal ash

    CN102153120B

  • Low-density ceramsite proppant prepared from utilization, and preparation method thereof

    CN105906318A

  • Preparation method of SiO2 aerogel

    CN106115722A

  • Coal-gangue-based ceramsite and preparation method thereof

    CN109809724A

  • Composite silicon carbide ceramic kiln furniture and preparation method thereof

    CN113213942A